Investigating transport in a tidally driven coral atoll flow using Lagrangian coherent structures. Issue 11 (5th October 2021) - Filippi, Margaux; Hadjighasem, Alireza; Rayson, Matt; Rypina, Irina I.; Ivey, Greg; Lowe, Ryan; Gilmour, James; Peacock, Thomas
Abstract: A field experiment study of flow transport around a coral reef was conducted at Scott Reef, an offshore atoll in the Timor Sea. A drifter deployment was designed based on the insight derived from two Lagrangian data analysis approaches, the finite‐time Lyapunov exponent method and the optimized‐parameter spectral clustering method, which were used to analyze the predictions of a numerical model. This analysis predicted the formation of a key transport barrier during a critical time of the tidal cycle that separated two bodies of water, one remaining trapped within the lagoon, and one advected offshore; this transport structure had no clear signature upon inspection of the velocity fields and thus the use of Lagrangian methods was crucial. The observed drifter trajectories confirmed the predictions, with the drifters separating into two clusters, one on each side of the transport barrier. The results demonstrate how Lagrangian approaches elucidate the processes governing connectivity and water exchanges between atolls and the surrounding ocean.